Utilization of food waste-derived volatile fatty acids for production of edible Rhizopus oligosporus fungal biomass. (August 2020) - Wainaina, Steven; Kisworini, Afrilia Dwi; Fanani, Marizal; Wikandari, Rachma; Millati, Ria; Niklasson, Claes; Taherzadeh, Mohammad J.
Graphical abstract: Highlights: Rhizopus oligosporus was grown solely on food waste-derived VFAs. Four-fold biomass increase observed in fed-batch compared to batch cultivation. Of the consumed carboxylates, acetic acid was the most preferred. Maximum biomass yield of 0.21 ± 0.01 g dry biomass/g VFAs COD eq. consumed obtained. Highest protein content in the biomass reached 39.28 ± 1.54%. Abstract: Rhizopus oligosporus is an edible filamentous fungus that can contribute to meet the growing demand for single-cell protein. Volatile fatty acids (VFAs) are favorable potential substrates for producing R. oligosporus biomass due to their capacity to be synthesized from a wide range of low-value organic solid wastes via anaerobic digestion. The goal of this work was to cultivate R. oligosporus using food waste-derived VFAs as the sole carbon source. To maintain the requisite low substrate concentrations, the fed-batch cultivation technique was applied. This resulted in a four-fold improvement in biomass production relative to standard batch cultivation. Maximum biomass yield of 0.21 ± 0.01 g dry biomass/g VFAs COD eq. consumed, containing 39.28 ± 1.54% crude protein, was obtained. In the bubble-column bioreactors, the complete uptake of acetic acid was observed, while the consumptions of caproic and butyric acids reached up to 97.64% and 26.13%, respectively.